2012
DOI: 10.1038/modpathol.2012.111
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miRNAs and PTEN in endometrial specimens ranging from histologically normal to hyperplasia and endometrial adenocarcinoma

Abstract: We investigated the relationship between frequently deregulated microRNAs (miRNAs) and enodometrial pathology in an attempt to find the most dependable miRNA or combination of miRNAs to identify normal, hyperplastic and malignant endometrial tissues. We also investigated the association between those miRNAs and PTEN status. We measured the expression of six miRNAs (miR-21, 182, 183, 200a, 200c and 205) in 75 formalin-fixed, paraffin-embedded normal, hyperplastic, and malignant endometrial tissue blocks using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 41 publications
15
56
0
Order By: Relevance
“…48 We focused our analysis on postoperative FFPE EC primary tumors since it is known that FFPE specimens can be used for real-time PCR-based quantitative miRNA expression studies. 16 This meant we could draw on the entire specimen collection of the Pathology Department containing samples taken between 2003 and 2012, and select samples to form two groups fully respecting the matching criteria. However, to provide a diagnostic tool, this analysis should be validated on preoperative samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 We focused our analysis on postoperative FFPE EC primary tumors since it is known that FFPE specimens can be used for real-time PCR-based quantitative miRNA expression studies. 16 This meant we could draw on the entire specimen collection of the Pathology Department containing samples taken between 2003 and 2012, and select samples to form two groups fully respecting the matching criteria. However, to provide a diagnostic tool, this analysis should be validated on preoperative samples.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, there are few data about nodal status-associated miRNA regulation in EC, especially in women at low and intermediate risk. miRNAs, with their remarkable stability, can be studied in formalin-fixed paraffin-embedded (FFPE) specimens 16 and are promising biomarkers for tumor staging.…”
mentioning
confidence: 99%
“…Akiyama-Abe et al reported that expression of PTEN was lost in 56 endometrial carcinoma patients (25%) [17]. Heejeong et al showed that PTEN loss was significantly higher in endometrial carcinoma compared with simple hyperplasia (68% vs. 24%), and it was also higher in complex atypical hyperplasia compared with simple hyperplasia (71% vs. 24%) [18]. In our study, PTEN expression in endometrioid carcinomas was similar to that in atypical hyperplasias (p=0.14), suggesting that alterations in PTEN occur at a relatively early stage in endometrial tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN functions as a phosphatase and inhibits the growth factor signals transduced through PI3K by inhibiting AKT phosphorylation (Li et al 1998). Pten mutations are observed in 30-80% of type 1 ECs and in 20-70% of complex atypical hyperplasia, a premalignant stage of EC (Tashiro et al 1997, Levine et al 1998, Lee et al 2012. Global homozygous PTEN inactivation is embryo lethal and the mice die between gestation days 6.5 and 9.5 .…”
Section: Introductionmentioning
confidence: 99%